The Impact of Globalization with its Different Aspects on Economic Growth: The Case of Turkey - Cestepe, Hamza; Ergün Tatar, Havanur; Erdogan, Serdar; Tatar, Havanur Ergün (Istanbul Univ, 2023)
As a multi-dimensional concept that affects many other factors, globalization has a profound impact on the economy as well. It is possible to argue that developing countries are more affected by globalization than others. In this study, the impact of globalization on the various aspects of economic growth is analyzed empirically for Turkey, a developing country. The ARDL Bounds Test was applied as an econometric methodology, using the dataset period between 1970-2018 for Turkey. This study used economic, social, political, and overall globalization indices to measure globalization. The results show that social, economic, and political globalization affect economic growth positively, whereas the overall globalization index affects it negatively in the long run. The ARDL Bounds Test results show that the utilized variables in the study are co-integrated in the long run. In fact, there is an economic relationship between the variables.
The Impact of Globalization with its Different Aspects on Economic Growth: The Case of Turkey
Keywords: Globalization; Economic Growth; Turkey; Ardl Bounds Test